2013
DOI: 10.3109/02699052.2013.794968
|View full text |Cite
|
Sign up to set email alerts
|

Neurometabolic and microstructural alterations following a sports-related concussion in female athletes

Abstract: This study demonstrates persistent neurometabolic and microstructural alterations in female athletes suffering a sports-related concussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
67
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 56 publications
16
67
0
2
Order By: Relevance
“…For example, magnetic resonance spectroscopy (MRS) studies have demonstrated neurometabolic changes after SRC lasting up to 1 month postinjury. [6][7][8][9] Similarly, in a functional MRI study, hyperactivation of the dorsolateral prefrontal cortex was found to persist beyond 2 months postinjury in athletes whose symptoms subsided at 2 weeks after injury. 10 DTI studies demonstrating structural changes from repetitive concussive head impacts have been reported in ice hockey players over the course of a single season, 11 in athletes with prolonged symptoms, 12 as well as in adolescents exhibiting close-to-normal scores on the Sports Concussion Assessment Tool (SCAT2) 13 at 2 months postinjury.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…For example, magnetic resonance spectroscopy (MRS) studies have demonstrated neurometabolic changes after SRC lasting up to 1 month postinjury. [6][7][8][9] Similarly, in a functional MRI study, hyperactivation of the dorsolateral prefrontal cortex was found to persist beyond 2 months postinjury in athletes whose symptoms subsided at 2 weeks after injury. 10 DTI studies demonstrating structural changes from repetitive concussive head impacts have been reported in ice hockey players over the course of a single season, 11 in athletes with prolonged symptoms, 12 as well as in adolescents exhibiting close-to-normal scores on the Sports Concussion Assessment Tool (SCAT2) 13 at 2 months postinjury.…”
Section: Introductionmentioning
confidence: 86%
“…31 In college athletes exhibiting prolonged symptoms after SRC, increased MD has been reported in parts of the left inferior/superior longitudinal and fronto-occipital fasciculi, the retrolenticular part of the internal capsule, and posterior thalamic and acoustic radiations. 12 Persistent microstructural alterations in deep WM have been shown in female contact sports athletes at 7 months postinjury 6 ; all participants were symptom free at this point of their recovery, suggesting that, in female athletes, structural recovery may lag behind behaviorally assessed recovery by up to 7 months postinjury. Finally, changes in WM microstructure were observed in a cohort of contact sports athletes with subconcussive blows to the head (26-399 hits), whereas no such changes were identified in 6 control participants.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Changes in functional and structural connectivity in the brain, neurometabolism, and heart-rate variability have been observed at medical clearance in athletes with SRC (27)(28)(29)(30). In addition, we recently identified elevated peripheral blood chemokine levels in healthy athletes participating in collision sports (14).…”
Section: Introductionmentioning
confidence: 99%
“…По мнению авторов, детский мозг может иметь нейропротекторный механизм, которого нет у взрослых. Chamard Е. и коллеги [8] показали снижение креатина спустя семь месяцев после сотрясения в моторной зоне коры. У женщин отмечается более выраженное снижениe NAA/креатина на протяжении сезона по сравнению с мужчинами.…”
unclassified